Associations between parity, pregnancy loss, and breastfeeding duration and risk of maternal type 2 diabetes: An observational cohort study. Issue 11 (25th March 2021) - Huo, Yanan; Cheng, Lihong; Wang, Chenxiu; Deng, Ying; Hu, Ruying; Shi, Lixin; Wan, Qin; Chen, Lulu; Zeng, Tianshu; Yu, Xuefeng; Tang, Xulei; Yan, Li; et al.
Abstract: Background: Parity, pregnancy loss, and breastfeeding duration were found to be associated with diabetes. However, the results are inconsistent. Also, no epidemiological studies have examined the association of these reproductive factors with diabetes in the same large population. We aim to investigate the associations between parity, pregnancy loss, breastfeeding duration, and the risk of maternal diabetes in middle‐aged and elderly Chinese females. Methods: We included 131 174 females aged ≥40 years from the REACTION study (Risk Evaluation of Cancers in Chinese Diabetic Individuals: A Longitudinal Study). Multivariable linear regression and logistic regression were used to assess the association between parity, pregnancy loss, and breastfeeding duration and type 2 diabetes. Results: The number of parities and breastfeeding duration were positively related to fasting plasma glucose, 2‐hour postload glucose, glycosylated hemoglobin, and homeostatic model assessment of insulin resistance. Compared with those with one birth, nulliparous women or women with 2 or ≥3 births had a significantly increased risk of diabetes. The odds ratios (OR) and 95% confidence intervals (CI) were 1.27 (1.10‐1.48), 1.17 (1.12‐1.22), and 1.28 (1.21‐1.35), respectively. Compared with women without pregnancy loss, those who underwent 2 (OR 1.09; 95% CI, 1.04‐1.14) or ≥3 pregnancy losses (OR 1.11; 95% CI, 1.04‐1.18) had an increased risk of diabetes. Moreover, women with a breastfeeding duration ≥0 to 6 months (OR 0.82; 95% CI, 0.75‐0.90) and ≥6 to 12 months (OR 0.94; 95% CI, 0.89‐0.99) had a significantly lower risk of diabetes. Conclusions: Nulliparous women or women with multiparity or more than one pregnancy loss have an increased risk of diabetes in later life, while women who breastfeed more than 0 to 12 months have a lower risk of diabetes. Abstract : Highlights The number of parities and breastfeeding duration were positively related to fasting plasma glucose, 2‐hour postload glucose, glycosylated hemoglobin, and homeostatic model assessment of insulin resistance. Women who were nulliparas or had more than one birth or experienced more than one pregnancy loss had an increased risk of diabetes. On the other hand, women who breastfed for less than 12 months had a lower risk of diabetes. Interaction effects between parity and pregnancy loss with body mass index or age， and breastfeeding duration with menopause status were detected for the risk of diabetes. 摘要: 背景: 胎次、流产和母乳喂养时间被认为与糖尿病风险相关, 但相关研究结果并不一致。此外, 尚无流行病学研究在同一人群中评估这些生育因素与糖尿病的相关性。本文旨在研究中国中老年女性的胎次、流产、母乳喂养时间与未来2型糖尿病风险之间的关系。 方法: 本研究纳入REACTION(中国2型糖尿病患者肿瘤发生风险)研究中131174名年龄≥40岁的女性, 采用多元线性回归分析和logistic回归分析评估胎次、流产和母乳喂养时间与2型糖尿病风险之间的关系。 结果: 胎次数和母乳喂养时间与空腹血糖、餐后2小时血糖、糖化血红蛋白及胰岛素抵抗的稳态模型评估呈正相关。与生育1胎的妇女相比, 未生育妇女或生育2胎或≥3胎的妇女患糖尿病的风险显著增加, 优势比(OR)和95%置信区间(CI)分别为1.27(1.10‐1.48)、1.17(1.12‐1.22)和1.28(1.21‐1.35)。与没有流产的女性相比, 经历2次(OR 1.09；95% CI, 1.04‐1.14)或≥3次流产(OR 1.11；95% CI, 1.04‐1.18)的女性, 糖尿病风险显著增加。 此外, 母乳喂养时间0 6个月(OR 0.82；95% CI, 0.75‐0.90)和6 12个月(OR 0.94；95% CI, 0.89‐0.99)的妇女, 糖尿病风险显著降低。 结论: 未生育、多胎或不止一次流产的妇女糖尿病风险增加, 而母乳喂养0 12个月妇女, 糖尿病的风险较低。